20 kWe Biomass Downdraft Gasifier System - Ishak, Mohd Asrul (Universiti Sains Malaysia, 2005)
A small scale downdraft gasifier that has producing 20kW biomass generator had been set to provide electrical power for the rural areas have been developed. The downdraft gasifier is erected in the laboratory at the School of Mechanical Engineering, Universiti Sains Malaysia (USM). In this research, gasification system in used is gasifier in lower flow with a wood as a biomass sources. Many modification were made during installation and this experimented to make it suit with surrounding condition and to improve the performance of the system. Experiments have been performed of gasification of furniture wood as raw material. The system performance of the gasifier had been determined by finding the efficiency of the system, moisture content and diesel displacement. The system of the downdraft gasifier also involved the development of power absorbing system using 24 kW electrical loading as heating element has been successfully done. The overall efficiency of the system at full speed is 3.64% to 15.75% and minimum speed is 4.16% to 21.5% depending on the electrical load used to absorb the power from the generator. Air flow rate of the producer gas also increase with the speed of generator. The moisture content of the wet wood is quite small but still in the range.